Toward the Role of L2 Enjoyment in EFL Students' Academic Motivation and Engagement - Liu, Shanshan (Frontiers in Psychology, 2022)
Abstract Since students’ academic success is tied to their academic motivation and engagement, determining the predictors of these two variables seems critical. So, several inquiries have inspected the role of students’ emotional and personal variables in their academic motivation and engagement. Nonetheless, the function of L2 enjoyment as an important emotional factor has remained elusive. Moreover, no inquiry has reviewed this issue neither systematically nor theoretically. To fill these lacunas, this review study aims to explain definitions, dimensions, and theoretical frameworks of L2 enjoyment, student academic motivation, and student academic engagement. This study also intends to outline the positive consequences of L2 enjoyment for students’ academic engagement and motivation. Relying on the theoretical and empirical evidence, the positive role of L2 enjoyment in raising EFL students’ engagement and motivation was firmly affirmed. Finally, the implications of the findings are discussed.